Performance of combined ARQ with SR and GBN for broadband wirelesssystems on a 40 GHz band radio channel. - Fukui, N. (IEEE Communications magazine)
Mobile wireless communication systems for the fourth generation are being explored. The key is broadband and high-quality communications to support multimedia services, and the use of millimeter or centimeter-wave band and ARQ is being considered to realize such communications. In this article we propose a new ARQ scheme which is combined with SR and GBN, and confirm that this new scheme is proper for broadband communication systems. We implemented our ARQ function with hardware and evaluated the ARQ performance: throughput, cell loss rate, and cell transfer delay on a pseudo Rayleigh fading channel. In addition, we evaluated ARQ performance on an actual 40 GHz band radio channel. Through the evaluation, we found it necessary to design an ARQ scheme in accordance with system requirements, and our combined ARQ satisfies this required condition